Tantangan dan Peluang Sertifikat Elektronik dalam Reformasi Pendaftaran Tanah di Era Digital. - Syarifaatul Hidayah; Evi Hariyani; Lilis Mukarromah; Aprila Niravita; M. Adymas Hikal Fikri (JURNAL ILMIAH NUSANTARA, 2024)
Land registration reform in the digital era brings new innovations in the form of electronic certificates that aim to improve the efficiency, accuracy and security of land ownership data. There are various possibilities for electronic certificates: B. Speed up the land registration process, reduce the risk of document forgery, and facilitate data access to stakeholders through an integrated system. However, the implementation of electronic certificates also faces several challenges, including concerns about the security of digital data, gaps in access to technology between regions, and community resistance to changes in traditional systems. This article discusses the opportunities and challenges of electronic certificates in land registration reform in Indonesia. The focus is on efforts to improve digital infrastructure readiness, necessary regulations, and public education so that adaptation to electronic certificates can be effective and comprehensive. This research uses a normative legal approach with the aim of examining legislation and legal norms regarding the application of electronic certificates in land registration reform in the digital era. The approach used includes a legal approach that focuses on analyzing the Agrarian Law, the Regulation of the Minister of ATR/BPN on Electronic Certificates, and other regulations that underlie the use of digital technology in land management. The application of electronic land certificates by the Ministry of ATR/BPN is part of the Agrarian Reform Program which aims to accelerate, secure, and simplify the land registration process.